3D scene reconstruction method based on image optical flow feedback. (15th June 2021) - Su, Yulin
When the traditional method is used for 3D reconstruction of a 3D scene, the noise in the scene image cannot be effectively removed, the reconstruction efficiency is low, and the reconstruction accuracy is low. Therefore, a 3D reconstruction method based on optical-flow feedback is proposed to build the camera mathematical model. The weighted least square method is used to denoise the scene image based on the camera mathematical model. Based on the relationship between the optical-flow and the scene flow, the optical-flow is used to calculate the scene flow vector through the grid adjustment algorithm, and the rough grid is adjusted according to the calculation results to realise the 3D reconstruction of the three-dimensional scene. The experimental results show that the proposed 3D scene reconstruction method has good image denoising effect, high reconstruction efficiency and high reconstruction accuracy.